Perancangan Komik Digital Scrambled Egg sebagai Media Edukasi Keluarga Single Parent - Debora Audrey Sentosa (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2021)
Family is required for children’s character building, since they are the next generation of this world. However, many families nowadays failed in performing their task, indicated by the increasing numbers of marriage divorce in Indonesia. It has impacts drives them lonely, frustated, and depressed, leads them to do harmful things. Self-awareness is needed to solve this internal problem. Thus, the effective and efficient learning media of single parent family education is created in digital comics form, which will be published in LINE Webtoon. Synectics exploration method is applied, by receiving some written and verbal ideas to construct the visual appearance and Scrambled Egg’s storyline. Therefore, the writer designed Scrambled Egg comics that contains the five episodes of slice of life story about adolescent conflicts under broken home family, published once a week in LINE Webtoon. It is drawn in bishoujo (girly) style and written in Bahasa, improved with Malang dialect.